2014
DOI: 10.1504/ijmdm.2014.058470
|View full text |Cite
|
Sign up to set email alerts
|

Relevant information, personality traits and anchoring effect

Abstract: Abstract:Although personality has been one of the most-studied factors in management and decision-making research, this stream of research has generated inconsistent support for the relationship between personality traits and individuals' susceptibility to heuristics, and therefore biased judgment. The aim of this study is to investigate how the provision of correct information and individual difference factors influence susceptibility to anchoring effect. To test this hypothesis, individual levels of the pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 75 publications
0
38
0
1
Order By: Relevance
“…However, the Hans-Reyna model suggests that when anchors provide meaningful information to decision makers, they are likely to have greater influence on decision making through helping impart meaning and context to numbers and facilitate the allocation of a number to a gist judgment. This is supported by literature showing stronger effects of anchoring in terms of consumer purchases when the anchor used is a plausible price (Sugden et al, 2013) and greater reliance on relevant compared with irrelevant anchors when multiple anchors are presented (Caputo, 2014;Whyte & Sebenius, 1997). In the courtroom, jurors have been found to rely less on damage award requests that are not supported by evidence (Diamond et al, 2011), and meaningful anchors have been shown to have a greater influence on damage award decision making than meaningless anchors (Reyna et al, 2015;Hans et al, 2018).…”
Section: Replicating Predicted Benefits Of Numeracymentioning
confidence: 62%
“…However, the Hans-Reyna model suggests that when anchors provide meaningful information to decision makers, they are likely to have greater influence on decision making through helping impart meaning and context to numbers and facilitate the allocation of a number to a gist judgment. This is supported by literature showing stronger effects of anchoring in terms of consumer purchases when the anchor used is a plausible price (Sugden et al, 2013) and greater reliance on relevant compared with irrelevant anchors when multiple anchors are presented (Caputo, 2014;Whyte & Sebenius, 1997). In the courtroom, jurors have been found to rely less on damage award requests that are not supported by evidence (Diamond et al, 2011), and meaningful anchors have been shown to have a greater influence on damage award decision making than meaningless anchors (Reyna et al, 2015;Hans et al, 2018).…”
Section: Replicating Predicted Benefits Of Numeracymentioning
confidence: 62%
“…Their findings suggest that entrepreneurs are more prone than managers to use biases and heuristics. The bounded rationality of individuals' decisionmaking processes is a widely studied topic in management studies (Caputo, 2014). Busenitz and Barney (1997) maintain that future research should examine whether the use of biases and heuristics in strategic decision making remains stable over time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the past 40 years, researchers have established how emotions affect decision-making as well as estimations in competition: They reduce the utilization of cue utilization ( Easterbrook, 1959 ; Scherer & Oshinsky, 1977 ), increase discrimination of quantity ( Baker et al, 2013 ), improve the perception of the situation regardless of negative feedback ( Staw, 1981 ), and facilitate coping with conflict ( Behrendt & Ben-Ari, 2012 ; Marceau et al, 2015 ) as well as competition neglect ( Camerer & Lovallo, 1999 ) 1 . A large part of the literature demonstrates that emotions and decision-making are interweaved, including the domain of anchoring effect ( Furnham & Boo, 2011 ), personality traits ( Caputo, 2014 ), social power ( Overbeck & Droutman, 2013 ), anger ( Tsai & Young, 2010 ), and anticipated regret ( Hoelzl & Loewenstein, 2005 ; Wong & Kwong, 2007 ). Emotions can lead to greater selfanchoring while negative affectivity ( Bodenhausen et al, 2000 ) and experienced regret ( Sagi, 2006 ) inhibit self-anchoring.…”
Section: Theoretical Backgroundmentioning
confidence: 99%